Oral Anticoagulation and Mortality in Cases with Intracranial Bleeding: Analysis of Nationwide Prescription and Hospitalization Data - Kröger, Knut; Heldt, Fabian; Feyen, Ludger; Feller, Kathrin; Kowall, Bernd; Stang, Andreas (Hämostaseologie, 2024)
Objectives To demonstrate the safety of direct oral anticoagulants in relation to intracranial bleeding (ICB), we compared the number of patients taking anticoagulants in all cases of hospitalization and cases of hospitalization for ICB over time in Germany. We analyzed the intrahospital mortality of ICB cases in relation to long-term use of anticoagulants (LUAs).We performed a retrospective registry analysis of nationwide German hospitalizations including all hospital admissions and admission for ICB in patients aged ≥60 years in the period from 2006 to 2020 and separated for LUAs.Results In 2006, the age-standardized rate of hospitalized male patients with LUAs was 7.3% and that of female patients was 5.6%. In 2020, the rates increased to 22.0 and 17.7% for male and female patients, respectively. Among patients hospitalized for ICB in 2006, 7.0 and 5.6% were male and female patients with LUAs, respectively. In 2020, the rate increased to 13.7% for males and 10.8% for females.In 2006, age-standardized mortality rates of male and female patients with ICB without LUAs were 24.1 and 23.9%, respectively. In 2020, the rate slightly decreased to 22.7% in males, but it remained almost unchanged in females at 23.8%. In the cases with LUA, the mortality rate decreased from 30.1 to 24.3% in males and from 28.4 to 24.2% in females in the same period.Conclusion LUA seems to be safe because there is a slower increase of the rate of LUAs in ICB cases than in generally hospitalized cases in the period from 2006 to 2020. In addition, mortality in ICB cases with LUA tends to decrease compared to cases without LUA.
Keywords: intracerebral bleeding; vitamin K antagonists; direct oral anticoagulants; hospitalization; mortality